2006
DOI: 10.1016/j.hisfam.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Family reproduction and stem-family system: From Pyrenean valleys to Norwegian farms

Abstract: The article presents a comparative study of two stem-family European systems: on the one hand, the well-known central Pyrenean family as found in the Barony of Esparros, and, on the other hand, the one prevalent in highland farms of South-East Norway. In the two communities, the continuity of the "house" was maintained over generations through non-egalitarian practices of transmission to a privileged heir or heiress. Other siblings received compensations or stayed at home unmarried. Comparing long-term mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…At this point it is reasonable to consider a stem family as the social norm, at least in the villages of Klein and Gross Paniow (Fauve-Chamoux, 2006). The discussion of differences and commonalities in the family pattern among Bujakow villages may also benefit from structural analysis of the households' developmental cycles.…”
Section: And 4)mentioning
confidence: 99%
“…At this point it is reasonable to consider a stem family as the social norm, at least in the villages of Klein and Gross Paniow (Fauve-Chamoux, 2006). The discussion of differences and commonalities in the family pattern among Bujakow villages may also benefit from structural analysis of the households' developmental cycles.…”
Section: And 4)mentioning
confidence: 99%
“…Studies of marriage behaviour have suggested that an explanation for these local disparities can be found in community characteristics, showing that cultural norms, economic opportunities, History of the Family 15 (2010) 316 -332 availability of partners, and the degree to which young adults faced parental or social control were crucial factors determining marital behaviour (Engelen & Hillebrand, 1986;Engelen & Kok, 2003;Fauvre-Chamoux, 2006;Gjerde & McCants, 1995;Lloyd & South, 1996;South & Baumer, 2000;Van Poppel, 1992). So far, however few studies have investigated the effects of community context on marriage behaviour systematically, on the basis of a wide range of characteristics, a large number of communities, and over a very long period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we could also guess that illegitimacy was something like a concession to the landless, a social option, cushioning the consequences of a niche system [for such strategies cf. Fauve-Chamoux (1995, 2006]. In that sense, theses claiming a higher degree of sexual promiscuity for the servants and theses underlining the demand for more labour force during the times of agrarian reform to explain the increase in illegitimacy since about 1770 seem to be combinable.…”
Section: Final Discussionmentioning
confidence: 99%
“…all over western, northern and central Europe, especially, but not exclusively, associated with mountainous environments (cf. Berkner, 1977Berkner, , 1990Berkner & Mendels, 1978;Fauve-Chamoux, 1995, 2006Mitterauer, 1995;Ortmayr, 1995;Devos & Kennedy, 1999). Concerning the Alpine regions, we should discuss Ausgedinge households (cf.…”
Section: Introductionmentioning
confidence: 99%